2022
DOI: 10.1155/2022/6544514
|View full text |Cite
|
Sign up to set email alerts
|

Gingiva-Derived Mesenchymal Stem Cells Attenuate Imiquimod- (IMQ-) Induced Murine Psoriasis-Like Skin Inflammation

Abstract: Human gingiva-derived mesenchymal stem cells (GMSCs) are isolated from the gingival propria with promising regenerative, immunomodulatory, and anti-inflammatory properties. Recently, several studies, including ours, have found that GMSCs have the therapeutic potentials of nerve regeneration and skin disorders in various types such as the cell itself, cell-free conditioned medium, or extracellular vesicles (EVs). However, the mechanobiological behavior of GMSCs is closely related to the culture conditions. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Ye et al. found that intravenous administration of human gingiva-derived MSCs in mice (2 × 10 6 cells) can reduce the levels of pro-inflammatory cytokines including IFN-γ, TNF-α, IL-6, IL-17A, and IL-21 secreted by Th1 and Th17 cells and promote the increasing number of Treg cells in mouse psoriasis-like models ( 21 ). However, studies on the application and comparison of different types of MSCs in skin inflammatory diseases are still lacking.…”
Section: The Effects Of Mscs From Different Resources On Ad and Psori...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Ye et al. found that intravenous administration of human gingiva-derived MSCs in mice (2 × 10 6 cells) can reduce the levels of pro-inflammatory cytokines including IFN-γ, TNF-α, IL-6, IL-17A, and IL-21 secreted by Th1 and Th17 cells and promote the increasing number of Treg cells in mouse psoriasis-like models ( 21 ). However, studies on the application and comparison of different types of MSCs in skin inflammatory diseases are still lacking.…”
Section: The Effects Of Mscs From Different Resources On Ad and Psori...mentioning
confidence: 99%
“…Xiong et al found that subcutaneous or intravenous administration of MSCs isolated from human exfoliated deciduous teeth (SHEDs), a special type of MSCs with superior capability of immunoregulation, in mice (2 × 10 6 cells) can effectively improve the disruption of skin barrier function and enlarged spleens, decrease the levels of IgE and TLSP, and inhibit the activation of Th1, Th2, and Th17 cells in skin lesion (57). Moreover, Ye et al found that intravenous administration of human gingiva-derived MSCs in mice (2 × 10 6 cells) can reduce the levels of pro-inflammatory cytokines including IFN-g, TNF-a, IL-6, IL-17A, and IL-21 secreted by Th1 and Th17 cells and promote the increasing number of Treg cells in mouse psoriasis-like models (21). However, studies on the application and comparison of different types of MSCs in skin inflammatory diseases are still lacking.…”
Section: Mscs From Other Resourcesmentioning
confidence: 99%
See 1 more Smart Citation